Analisis Perhitungan Kebutuhan Sistem pada Perancangan Pembangkit Listrik Tenaga Surya (PLTS) Rumah Tangga 900 Watt - Rachmad Ady Setiawan; Laga Erlangga Cendekia; Arwanti Saputri; Nisa Saju Fernanda (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research aims to design a Solar Power System (PLTS) for households that can meet an energy demand of 4.5 kWh per day. The system design takes into account the efficiency of solar panels and the average solar radiation potential in Semarang, which is around 5 hours per day. The method used in this research involves calculating the required solar panel capacity based on the daily energy needs of the household, panel efficiency, and solar radiation hours. The calculation results show that the required PLTS capacity is 1125 Wp, which is then designed using 4 solar panels with a capacity of 300 Wp each. This system is expected to allow households to meet their energy needs independently and sustainably. The implication of this research is to provide an alternative solution for households in reducing their dependence on conventional energy sources, while contributing to the effort to reduce greenhouse gas emissions.